An epidemiological study of burn cases admitted to a tertiary care centre of Odisha - Panda, Srikanta; Mohapatra, Minati; Jena, Unmesh Kumar; Kar, Preetam Kumar; Sarangi, Anshuman; Jena, Somnath; Sarangi, Ashok Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: India, has an estimated annual incidence of 6-7 million burn cases. In the state of Odisha, there are very few epidemiological studies of Burn injuries. Therefore a hospital based descriptive study among the admitted burn cases was conducted. Methods: The study was conducted among the burn cases admitted to the burn unit of Surgery Department of SCB Medical College and Hospital, Cuttack during the time period from 1st January 2014 to 31st May 2015.A total of 145 patients were included for the study. Results: Socio-demographic profile of burn cases showed 83 (57.2%) were females and rest 62 (42.8%) were males. Regarding residence, 109 (75.1%) of the burn victims were from rural area and the rest 36 (24.9%) were from urban area. Also 140 cases (96.5%) belonged to low socio-economic status and were having BPL card. Regarding the nature of burn, 108 (74.5%) cases had it accidentally while 33 (22.7%) had burn due to suicidal attempt and the rest 4 (2.8%) had homicidal burn and all these 4 cases were married females. 104 (71.7%) cases were affected by flame, 12 (8.2%) cases were due to scald while 29 (20%) were due to electric burn. Among the burn cases due to flame, kerosene was the most common cause. Conclusions: The study revealed that thermal burn was the most common type of burn and the victims were in their active productive period of life (21-40 years), married, illiterate and were from rural areas. Among the thermal burn victims, use of kerosene was the most common cause of burns in both the sexes.